Antimicrobial activity of bacterial endophytes isolated from Aconitum nagarum Stapf ,a medicinal plant of North East Indo-Burma belt - Mangkhom Sonika Devi; Subham Saha; Kumananda Tayung (Brazilian Journal of Microbiology, 2026)

Exploring the climate-driven dynamics of whitefly (Bemisia tabaci) Asia-I cryptic species population and their role in mungbean yellow mosaic India virus (MYMIV) transmission in black gram - Subham Dutta; Moumita Panda; Kousik Atta; Poorvasandhya R; Thomas Wilbur Davis; Ankur Mukhopadhyay; Souvik Samanta; Poly Saha; Jayanta Tarafdar; Mritunjoy Barman (Phytoparasitica, 2026)

Spermidine Attenuates Neuroimmune Dysfunction in Gulf War Illness via Modulation of the Gut- Brain Axis - Ayushi Trivedi; Subhajit Roy; Madhura More; Dipro Bose; Punnag Saha; Ram Kumar; Subham Sarkar; Jonathan Skupsky; Ashok Tuteja; Kimberly Sullivan; Nancy Klimas; Saurabh Chatterjee (Molecular Neurobiology, 2026)
Gulf War illness (GWI) affects nearly one-third of US veterans deployed during the 1990–1991 Gulf War (GW) and is characterized by chronic fatigue, neuroinflammation, and gut dysbiosis. Through comprehensive fecal metabolomics sequencing, our lab previously reported the depletion of beneficial metabolites including spermidine in the preclinical GWI mouse model. Spermidine is an endogenously synthesized polyamine known for its anti-inflammatory and mucosal barrier protective effects in various pathological diseases. Given its established role in mitigating intestinal inflammation and maintaining homeostasis, this study investigated the therapeutic potential of spermidine in a persistent (22 weeks) GWI mouse model, with a specific focus on gut–brain axis regulation. Our results demonstrated that spermidine effectively restored both microbial richness and diversity by selectively enriching beneficial bacterial taxa and suppressing growth of opportunistic pathogens, which are otherwise dysregulated following exposure to GW chemicals. Spermidine treatment also improved gut epithelial barrier integrity and reduced epithelial release of high-mobility group box 1 (HMGB1) into systemic circulation. Recent studies on GWI have implicated a critical role of gut-derived damage-associated molecular patterns (DAMPs), particularly HMGB1 in mediating neuroinflammation. Our findings indicate that systemic levels of HMGB1 critically influence the extent of blood–brain barrier (BBB) disruption and subsequent microglial activation. Mechanistically, spermidine activated intestinal aryl hydrocarbon receptor (AhR)/nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling, which played a role in limiting intestinal HMGB1 release and suppressing downstream receptor for advanced glycation end-product (RAGE)–mediated microglial activation in the brain. In vitro results indicate spermidine promoted AhR/Nrf2 nuclear translocation which reduced LPS-induced HMGB1 release from primary intestinal epithelial cells (IECs), effects abrogated by AhR inhibition. Additionally, we observed that HMGB1 directly induces microglial activation via RAGE receptors in immortalized microglial (IMG) cell lines in a dose-dependent manner. These results demonstrate that spermidine decreases neuroinflammation by modulating gut–brain axis pathophysiology associated with GWI. Together, this study demonstrates the therapeutic role of spermidine in ameliorating systemic and neurological disturbances in GWI. Graphical Abstract

Influence of Potassium Management on Physiology and Biochemical Activities of Lentil (Lens culinaris M.) Grown Under Rainfed Condition in Different Tillage and Sowing Time Scenario - Ramprosad Nandi; Subham Mukherjee; Kh. Chandrakumar Singh; Madhumonti Saha; Priyanka Ghatak; Arnab Kundu; Subhadip Saha; Prasanta Kumar Bandyopadhyay; Rajib Nath (Journal of Soil Science and Plant Nutrition, 2025)

First report of Colletotrichum asianum causing anthracnose on Capsicum annuum in India - Subham Saha; Kumananda Tayung (Journal of Plant Pathology, 2025)

First report of Fusarium proliferatum causing leaf blight of chilli (Capsicum annuum) in India - Subham Saha; Kumananda Tayung (Crop Protection, 2025)

Existence of Thermotolerant and Salt-Loving Diarrheagenic Vibrio alginolyticus in Non-Saline Potable Water System: A Novel Finding from India - Suvajit Saha; Subham Mookerjee; Anup Palit (Current Microbiology, 2024)

Toxic heavy metal bioremediation potential of Pleurotus ostreatus fruit bodies grown in sugarcane bagasse supplemented substrate - Tirthankar Saha; Sagnik Das; Snigdha Sau; Debarpita Datta; Sourima Kundu; Subham Saha; Shreya Chakraborty; Bikram Dhara; Arup Kumar Mitra (Vegetos, 2024)

Exploring the dynamics of toxigenic environmental Vibrio mimicus and its comparative analysis with Vibrio cholerae of the southern Gangetic delta - Madhumanti Halder; Suvajit Saha; Subham Mookerjee; Anup Palit (Archives of Microbiology, 2022)

Preponderance of Multidrug-resistant, Toxigenic, and Thermotolerant Enteropathogenic Bacteria in Raw and Cooked Seafood of Indo-Gangetic Basin and Associated Health Risks - Suvajit Saha; Madhumanti Halder; Subham Mookerjee; Anup Palit (Journal of Aquatic Food Product Technology, 2020)